The application of derivatization and retention incides system for identification of alkylpolyethylene glycol ethers by capillary gas chromatography - Komárek, Karel; Richter, Pavel (Univerzita Pardubice, 2000)
This study deals with the possibility of GC analysis of individual alkylpolyethylene glycol ethers (APEGEs)C4-C10. The possibilities of derivatization reactions of these substances and the advantages of the derivative preparation are discussed. APEGEs were coverted into three types of derivatives: acetates, trifluoroacetates and trimethylsilyl ethers. The retention indices of individual oligomers of APEGEs and their derivaties for the column temperature programmed linearly were measured. The influence of an increase in the lenght of the chain in the alkyl orpolyoxyethylene glycol part of molecule of non-derivatized APEGEs and their derivatives on the retention indices was studied.
Keywords: plynová chromatografie; APEGEs; Identifikace; polyethery; derivatizace